Little Red - Sarah, Duchess of York Duchess of York, 1959-; Williams, Sam 1955- (New York : Simon & Schuster Books for Young Readers, 2003)
While on a picnic with four friends, a plucky doll named Little Red decides to investigate a noise that doesn't sound very friendly.
3-6.
Accelerated Reader AR